Nurses as Street Level Bureaucrats: Experiences from Diabetes Care Nurses in Kuwait - Alshammari, Muna; Nalubega, Sylivia (Open Journal of Nursing, 2021)
Street-level bureaucrats are described as public service workers who interact directly with citizens in the course of their work and who have substantial discretion in the execution of their work. This article is a reflection of the primary author’s doctoral research experience, which investigated the role of nurses in caring for long-term diabetes patients in two selected hospitals in Kuwait. Nurses working in diabetes care in Kuwait were reported to operate under difficult conditions and utilized the tool of discretion to provide patient care, hence were exemplary street-level bureaucrats.
Keywords: Nurses, Street-Level Bureaucrats, Diabetes, Kuwait